2021
DOI: 10.3892/etm.2021.10442
|View full text |Cite
|
Sign up to set email alerts
|

Advances in molecular mechanisms of pelvic organ prolapse (Review)

Abstract: Pelvic organ prolapse (POP) is a common gynecological benign disease occurring in middle-aged and elderly females. Its incidence increases every year. To date, the majority of studies investigating its etiology have not evaluated the underlying molecular mechanisms, which has caused substantial difficulties in the prevention, treatment and prognosis of POP. In the present narrative review, recent research studies concerning the molecular mechanisms of POP were systematically reviewed and the advances were summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 69 publications
0
11
0
3
Order By: Relevance
“…POP is primarily characterized by the weakening of support tissue and can be caused by pelvic floor connective tissue extracellular matrix remodeling, activation of oxidative stress, genetic susceptibility, denervation of pelvic floor innervation, and reduced estrogen infiltration ( Deng et al, 2021 ), however, the underlying mechanism, including the vital molecules and signaling pathways, is unknown. Furthermore, the role of regulatory ncRNAs in the pathogenesis of POP remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…POP is primarily characterized by the weakening of support tissue and can be caused by pelvic floor connective tissue extracellular matrix remodeling, activation of oxidative stress, genetic susceptibility, denervation of pelvic floor innervation, and reduced estrogen infiltration ( Deng et al, 2021 ), however, the underlying mechanism, including the vital molecules and signaling pathways, is unknown. Furthermore, the role of regulatory ncRNAs in the pathogenesis of POP remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changes in the extracellular matrix play an important role in the regulation of cell adhesion, proliferation, migration, and apoptosis through mechanical signal transduction ( Fiorentino et al, 2022 ). It is well known that remodeling of the ECM in the pelvic floor connective tissue is one of the reasons for the occurrence of POP ( Deng et al, 2021 ), particularly the proportions of collagen Ⅰ and Ⅲ ( Deprest et al, 2022 ). Ruiz-Zapata et al (2016) demonstrated that matrices increase stiffness in postmenopausal women with POP compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of C-OCE to assess the absolute stiffness values of the vaginal wall in prolapse may have high potential due to objective elasticity changes of the vaginal connective tissue. It is known that the predominant pathogenetic mechanism of POP is the decreased synthesis and the increased breakdown of the extracellular matrix in the connective tissue of the pelvic floor, with collagen being its main component [75]. Numerous mechanisms are responsible for the disruption in the balanced collagen metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Physiology frontiersin.org 06 Discussion POP is not life-threatening but has a significant impact on a patient's quality of life with its incidence increasing every year. It is well accepted that POP is associated with postmenopausal estrogen deficiency and overstretching of the pelvic floor lead by vaginal delivery (Deng et al, 2021). The current study found that overall growth rate of POP fibroblasts was significantly slower Frontiers in Physiology frontiersin.org than controls under culture conditions, and estrogen slightly increased cell proliferation of all the fibroblasts with the most prominent effect at physiological concentrations (10 −10 and 10 −9 M), and the enhancement was only observed at 24 h, perhaps because of the half-life of estrogen is about 24 h in the culture medium.…”
Section: Figurementioning
confidence: 99%